2007
DOI: 10.1002/ccd.21153
|View full text |Cite
|
Sign up to set email alerts
|

Rheolytic percutaneous thrombectomy for acute pulmonary embolism in a pediatric patient

Abstract: Acute massive pulmonary embolism can have significant hemodynamic effects in both adults and children. We describe the case of a 10-year-old boy who developed cardiogenic shock after suffering a massive pulmonary embolism. A significant thrombus burden was removed using a catheter-based strategy of rheolytic thrombectomy, leading to stabilization of the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…[261][262][263][264][265][266][267][268][269][270][271][272][273] There are no specifi c guidelines for the use of thrombectomy in children, but there is general consensus that the TE recurrence rate and risk of long-term vas-tive of whether the infant received no therapy, UFH, or LMWH, with ‫ف‬ 70% of affected kidneys having irreversible renal atrophy. 279 Approximately 20% of children had hypertension on long-term follow-up, and 3% of children developed chronic renal failure.…”
Section: Surgical Therapymentioning
confidence: 99%
“…[261][262][263][264][265][266][267][268][269][270][271][272][273] There are no specifi c guidelines for the use of thrombectomy in children, but there is general consensus that the TE recurrence rate and risk of long-term vas-tive of whether the infant received no therapy, UFH, or LMWH, with ‫ف‬ 70% of affected kidneys having irreversible renal atrophy. 279 Approximately 20% of children had hypertension on long-term follow-up, and 3% of children developed chronic renal failure.…”
Section: Surgical Therapymentioning
confidence: 99%
“…The most common complications with coronary artery thrombectomy are bradycardia and heart block . Bradycardia may be related to activation of vascular endothelium stretch receptors or adenosine release from red cell hemolysis .…”
Section: Discussionmentioning
confidence: 99%
“…Although catheter thrombectomy is used frequently in adults, there are few reports describing its use in pediatric patients. The Angiojet ® catheter has been used to remove thrombus from pulmonary arteries and aorto‐pulmonary shunts in neonates and children . A similar catheter, the X‐SIZER ® catheter system (eV3, Plymouth, MN), was used to treat a complete superior vena cava thrombus in a 4 year‐old child following a Fontan operation .…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of Morbidity with Other Case Series of PMT Morbidity in the present study is lower than what has been reported in prior case series. A review of the literature published to date using the Angiojet system for PMT of massive PE reveals 83 patients 11–15,17–30 . In 22% of those patients (18 of 83) some form of bleeding complication was reported such as bleeding–not further specified, hemoptysis, or the need for transfusion (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…The side with worse perfusion and apparent larger thrombus burden was targeted for PMT first. Following placement of a 0.035‐inch Magic Torque (Boston Scientific, Natick, MA) guidewire in the segmental artery, the Angiojet catheter (Xpeedior or DVX) was either advanced directly over the wire into the main pulmonary artery or through a prior placed French Mullins sheath, allowing for constant pulmonary arterial pressure measurement and intermittent hand injections of contrast dye into the pulmonary artery 15 . Multiple runs of PMT were performed only in vessels estimated to be greater than 6 mm in diameter.…”
mentioning
confidence: 99%